A method for segregating the optical absorption properties and the mass concentration of winter time urban aerosol. (December 2015) - Ajtai, T.; Utry, N.; Pintér, M.; Major, B.; Bozóki, Z.; Szabó, G.
Abstract: A novel in-situ, real time method for the determination of inherent absorption properties of light absorbing carbonaceous particulate matter and its possible application for source apportionment are introduced here. The method is deduced from a two-week campaign under wintry urban conditions during which strong correlation was found between aerosol number size distribution and wavelength dependent optical absorption coefficient ( AOC(λ) ), measured by a Single Mobility Particle Sizer (SMPS) and a multi-wavelength photoacoustic absorption spectrometer, respectively, while wood burning and traffic (i.e. fossil fuel burning) activity were identified to be the dominant sources of carbonaceous particulate. Indeed, during the whole campaign, regardless of the actual emission strength of the aerosol sources, the measured number size distributions were always dominated by two unimodal modes with Count Mean Diameter (CMD) of 20 and 100 nm, which could be correlated to traffic and wood burning activities, respectively. AAE ff, AAE wb (i.e. the Aerosol Angström Exponent of traffic and wood burning aerosol, respectively), σ ff (266 nm), σ ff (1064 nm), σ wb (266 nm) and σ ff (1064 nm) (i.e. the segregated mass specific optical absorption coefficients at two of the measurement wavelengths) were found to be 1.17 ± 0.18, 2.6 ± 0.14, 7.3 ± 0.3 m 2 g −1, 1.7 ± 0.1 m 2 g −1 3.4 ± 0.3 m 2 g −1 and 0.31 ± 0.08 m 2 g −1, respectively. Furthermore the introduced methodology can also disentangle and quantify the temporal variation of both the segregated optical absorptions and the segregated mass concentrations of traffic and wood burning aerosol. Accordingly, the contribution of wood burning to optical absorption of PM was found to be negligible at 1064 nm but increased gradually towards the shorter wavelengths and became commensurable with the optical absorption of traffic at 266 nm during the whole measurement period. Furthermore, the contribution of wood burning mass to CM (mass of carbonaceous particulate matter) was dominant regardless of the strength of the emission activity of traffic and wood burning during the whole measurement period. Highlights: We introduce a new method for the real time source apportionment of atmospheric aerosol. The method is deduced from a field measurement campaign. The method requires the measurement of size distribution and optical absorption. The applied instruments are a SMPS and a multi-wavelength photoacoustic absorption spectrometer.